Source Dependent Ginger Supplementation Alters Triglyceride Levels in ISA Brown Hens - Mohammed M. Zinalabidin (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The poultry industry faces pressure to reduce antibiotic growth promoters and adopt natural alternatives that support productivity and animal health. Specific background: Ginger (Zingiber officinale) is widely recognized for its bioactive compounds with hypolipidemic, antioxidant, and antimicrobial properties, but its chemical composition varies with geographical origin, which may affect its biological efficacy. Knowledge gap: Limited evidence exists on how different sources and dietary inclusion levels of ginger influence serum biochemical traits in laying hens. Aims: This study examined the effects of 1% and 2% dietary inclusion levels of Indian, American, Spanish, and South African ginger powders on serum glucose, cholesterol, triglycerides, and total protein in ISA Brown laying hens. Results: While glucose, cholesterol, and total protein levels were unaffected, triglycerides showed significant variation: 2% Spanish ginger reduced levels by 51% compared with control, whereas 1% American ginger increased levels by 35%. Pearson’s correlations revealed a moderate negative association between glucose and triglycerides (r = −0.563) and a positive association between triglycerides and protein (r = 0.553). Novelty: This is the first comparative analysis linking ginger’s geographical origin to serum lipid modulation in layers. Implications: Spanish ginger at 2% emerges as a promising natural additive for lipid control and sustainable poultry nutrition. Highlights: Spanish ginger at 2% significantly reduced serum triglycerides. Glucose, cholesterol, and protein levels were unaffected by treatments. Ginger’s geographical origin influences its metabolic effects in poultry. Keywords : Ginger, Egg Mass Layer, Feed Intake, Yolk Color.